A Compilation of Moored Instrument Data and Associated Oceanographic Observations. Volume XXX. Gulf Stream Extension and Norwegian Sea Overflow Intrusion Experiments, 1979 - 1980. - Levy,Ellen; Tarbell,Susan A; Fofonoff,N P (1982)
Current and temperature measurements are presented from instruments deployed during October and November of 1979, southeast of the Grand Banks in North Atlantic, between 37 N and 41 N and between 42 W and 47 W. The measurements were made as part of two concurrent experiments, the Gulf Stream Extension (GSE) and the Norwegian Sea Overflow Intrusion (NSOI) arrays. Data from the current meters are presented in statistical tables and graphically as scatter plots, histograms, progressive vector plots, spectral plots and time series plots. Filtered time series are shown in composite displays. Data from XBT, CTD and T/Ps are also presented graphically. This document includes 5 microfiche inserts.